ANÁLISE DAS RELAÇÕES INTERGOVERNAMENTAIS ENTRE ESTADOS E MUNICÍPIOS ATRAVÉS DA CONSTRUÇÃO DE UMA TIPOLOGIA DE MUNICÍPIOS: o caso da Lei Robin Hood em Minas Gerais - Jane Noronha Carvalhais (Universidade Federal do Maranhão, 2014)
The article take as reference the Robin Hood Law (RHL) that has as goal the improvement of life quality of Minas Gerais population through ICMS quote-part distribution decentralization, income deconcentration, allocation of local resources in social areas, increase in taxes, efficiency of local public expenditure, and creation of a partnership between state and counties. It asks if RHL would be reaching those goals, in addition to bibliographic and documental research, Quadrant Analysis Method is used to build counties typology according to poverty level and resources transferred. It also notes that the results show that criteria with low redistributive capacity or concentrators have relatively high weight, that poor counties get smaller amounts than the rich ones. It concludes that although RHL represents a step forward, it al so needs improvements for minimizing the high socioeconomic heterogeneity typical of Minas Gerais counties.